Bilingualism and linguistic ideology in the United States - Shevchenko, I.S.; Шевченко, І.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
У статті розглядаються питання білінгвізму і мовних прав людини у поліетнічній державі США. Наводиться огляд законодавчої бази США та ООН у царині мовних прав людини. Мовна політика в поліетнічному суспільстві трактується як прояв боротьби еліт за владу. Аналіз історії та сучасного стану мовної політики в США доводить, що білінгвізм не загрожує національній єдності, а навпаки стимулює розвиток суспільства. В статье рассматриваются вопросы билингвизма и языковых прав человека применительно к полиэтническому государству США. Дается обзор законодательной базы США и ООН в области языковых прав человека. Языковая политика в полиэтническом обществе трактуется как проявление борьбы элит за власть. Анализ истории и современного состояния языковой политики в США доказывает, что билингвизм не угрожает национальному единству, а наоборот, стимулирует развитие общества. This article discusses issues of bilingualism and linguistic human rights in the USA as a multiethnic country. It provides an overview of the legal framework the U.S. and the UN in the area of linguistic human rights. Linguistic ideology in a multiethnic society is treated as a manifestation of the elites’ struggle for power. The analysis of the history and current state of linguistic ideology in the United States shows that bilingualism does not threaten national unity, but rather stimulates development of the society.
Білінгвізм і мовна політика в США
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; білінгвізм; боротьба еліт; влада; мовна політика; мовні права людини; bilingualism; linguistic ideology; linguistic human rights; struggle of elites; power